2021
DOI: 10.1523/jneurosci.1105-21.2021
|View full text |Cite
|
Sign up to set email alerts
|

Common and Unique Inhibitory Control Signatures of Action-Stopping and Attentional Capture Suggest That Actions Are Stopped in Two Stages

Abstract: The ability to stop an already initiated action is paramount to adaptive behavior. Much scientific debate in the field of human action-stopping currently focuses on two interrelated questions. (1) Which cognitive and neural processes uniquely underpin the implementation of inhibitory control when actions are stopped after explicit stop signals, and which processes are instead commonly evoked by all salient signals, even those that do not require stopping? (2) Why do purported (neuro) physiological signatures o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 61 publications
8
41
0
Order By: Relevance
“…However, its highest classification accuracy was between 400 ms and 600 ms, coincident with the P3 component. This observation is in accordance with a recent study using multivariate pattern analysis, that found that ERPs evoked by Stop signal could be decoded from “ignore” signals (analogous to our CGo signals) from 180 ms after signal onset, although better classification accuracy was observed at P3 latencies (Tatz et al, 2021 ). Finally, an interesting finding is that the peak in decoding accuracy in the imagined condition reached levels similar to those observed in the overt condition, suggesting that the ability to discriminate between CGo and Stop EEG signals is also maintained in mental rehearsal.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, its highest classification accuracy was between 400 ms and 600 ms, coincident with the P3 component. This observation is in accordance with a recent study using multivariate pattern analysis, that found that ERPs evoked by Stop signal could be decoded from “ignore” signals (analogous to our CGo signals) from 180 ms after signal onset, although better classification accuracy was observed at P3 latencies (Tatz et al, 2021 ). Finally, an interesting finding is that the peak in decoding accuracy in the imagined condition reached levels similar to those observed in the overt condition, suggesting that the ability to discriminate between CGo and Stop EEG signals is also maintained in mental rehearsal.…”
Section: Discussionsupporting
confidence: 93%
“…This idea is in line with the theory that surprise is accompanied by automatically engaged motor inhibition (Iacullo et al, 2020 ; Wessel & Aron, 2017 ); and also with the model “pause‐then‐cancel” which proposes that inhibition occurs in two steps. A first step, “pause”, which is initially activated after the presentation of surprising stimuli; and a second step, “cancel” (or continue for the case of CGo signals), that occurs after further evaluation of the stimuli (Schmidt & Berke, 2017 ; Tatz et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The absence of a significant P3 when evaluating the IC-D activity in the rhythmic experiment or, inversely, the IC-R activity in the discrete one suggests that the P3 signature is specific to the engaged inhibition brain component. This pattern of findings indicates that P3 is a clear-cut neural marker of action inhibition in the context of stop-signal reactions (Fine et al, 2020;Hynd et al, 2021;Tatz et al, 2021;Wessel & Aron, 2015). In addition, an N2 wave was exclusively evoked by the IC-R in the rhythmic ABORT R but not in any other condition.…”
Section: [Fig 6] [Table 1] Discussionmentioning
confidence: 70%
“…Crucially, however, any attempt to disentangle the domain-general detection of a salient stimulus from the stopping-specific implementation of inhibitory control is complicated by another factor. Namely, all salient stimuli, even those presented outside of stop-signal contexts, lead to an automatic, physiological inhibition of the motor system (Dutra et al, 2018; Tatz et al, 2021; Wessel, 2018; Wessel & Aron, 2017). For example, salient stimuli lead to a non-selective inhibition of cortico-motor excitability (Iacullo et al, 2020), activate basal ganglia regions involved in inhibitory pathways (Wessel et al, 2016), reduce isometrically exerted force (Novembre et al, 2018, ; 2019), and increase motoric response times (e.g., Parmentier, 2008).…”
Section: Discussionmentioning
confidence: 99%